Effects of Isometric Biceps Exercise on Blood Pressure in Adults with Hypertension - Silva, Paulo Henrique Medeiros; de Brito, Leandro Campos; Cabral, Ludmila Lucena Pereira; Farias-Junior, Luiz Fernando; Browne, Rodrigo Alberto Vieira; Vianna, Lauro C.; Costa, Eduardo Caldas (International Journal of Sports Medicine, 2021)
We investigated the acute effects of isometric biceps exercise on resting and ambulatory blood pressure in hypertensive adults. A total of 12 medicated hypertensive adults (aged 47±7 years; body mass index 27.2±2.7 kg/m2; resting blood pressure 123±12/74±6 mmHg) performed an isometric biceps exercise session (bilateral biceps exercise; 4×1 min at 30% of 1-RM, 2 min recovery) and a control session (without exercise) in a randomized order separated by a 7 to 10-day period. Resting blood pressure, heart rate, and heart rate variability indexes (SDNN, RMSSD, LF, HF, and LF/HF) were measured pre- and up to 30 min post-sessions. Next, ambulatory blood pressure was monitored during 22-hour post-sessions (awake and asleep periods). No significant changes were observed for resting blood pressure, heart rate, or heart rate variability indexes up to 30 min post-sessions (p>0.05). Furthermore, no significant differences were observed in average ambulatory blood pressure values in 22-hour (126±11/71±6 mmHg vs. 126±15/71±9 mmHg), awake (127±10/74±6 mmHg vs. 130±14/75±10 mmHg), and asleep (123±15/68±6 mmHg vs. 120±17/66±9 mmHg) periods between the control and isometric sessions, respectively (p>0.05). In conclusion, an isometric biceps exercise session does not elicit an acute antihypertensive effect in adults with hypertension, which suggests that its prescription to improve the acute BP control is limited.
Keywords: resistance training; post-exercise hypotension; heart rate